Increasing role of three-point field goals in National Basketball Association - Jaguszewski, Maciej (Akademia Wychowania Fizycznego w Poznaniu)
Introduction. Since introduction of three-point field goal NBA teams have used this shot more frequently and nowadays it is inseparable part of teams’ game plan in basketball. The increasing role of three-point shot is recently topic of many conversation around basketball. Aim of Study. The purpose of this study was to examine if the growth of the role of three-point shots in the NBA is statistically significant, to find out the reason for that growth and whether three-point field goal attempts have an impact on result of basketball games. Material and Methods. Statistical data concerning three-point field goal attempts over the course of 15 most recent NBA regular seasons were collected and used in analysis. Increasing role of three-point shot was examined by original method, using 3PA/FGA coefficient which measures the frequency of three-point field goal attempts in all field goal attempts. Statistical calculations were carried out using STATISTICA software package. Results. Statistically significant differences in frequency of three-point field goal attempts between seasons taken in consideration were revealed by Friedman’s ANOVA. Results also showed that the biggest increase of frequency of three-point shots was between 2015/16 and 2016/17 seasons after the most successful regular season in NBA history by Golden State Warriors. Conclusions. Three-point field goal became one of the most important part of basketball and its role has increased over the years. Nowadays ability to shoot from beyond the arc is crucial as lack of this ability decreases number of options in offensive tactic by any team. Even though three-point field goal is not the most important factor in determining winner of basketball game, it has significant impact on result of basketball games.
Keywords: three-point field goal; basketball; National Basketball Association; trend in sport